The non-uniform communication performance of adaptive routing for hierarchical interconnection network for 3D VLSI - Miura, Yasuyuki; Watanabe, Shigeyoshi; Rahman, M.M. Hafizur (Society for Science and Education (SSE), United Kingdom, 2015)
The Tori-connected mESH (TESH) Network is a k-ary n-cube networks of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher level k-ary n-cube networks. Many adaptive routing algorithms for k-ary n-cube networks have already been proposed. Thus, those algorithms can also be applied to TESH network. We have proposed three adaptive routing algorithms - channel-selection, link-selection, and dynamic dimension reversal - for the efficient use of network resources of a TESH network to improve dynamic communication performance.